Welded joint

By containing Si and Al in the steel plate and controlling the surface state in high dew point annealing, the C concentration of the steel plate surface layer is reduced, and the problem of LME cracking during welding joints is solved, and high LME resistance and welding performance are improved.

CN119836485APending Publication Date: 2025-04-15NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380063817.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-09-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the manufacture of welded joints, liquid metal embrittlement (LME) cracking leads to a decrease in weldability, and the prior art is difficult to effectively suppress this problem.

Method used

By containing a large amount of Si and Al in the steel plate and controlling the surface state during high dew point annealing, oxygen diffusion into the material is promoted, and the C concentration of the steel plate surface layer is reduced, thereby stabilizing ferrite and inhibiting LME cracking.

Benefits of technology

High LME resistance during the manufacture of welded joints is achieved, low C concentration around the welded part is ensured, and the overall performance of welded joints is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836485A_ABST
    Figure CN119836485A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a welded joint in which LME cracking during production is suppressed. This welded joint is characterized in that the plated steel sheet constituting the welded joint has a prescribed chemical composition, and the depth at which the C concentration measured by GDS in the depth direction of the base material is 0.05% or less is 5 [mu] m or more, starting from the interface between the plating layer and the base material steel sheet in the non-heat-affected portion of the plated steel sheet. The roughness (Ra) of the interface between the plating layer and the base material steel sheet in the cross section of the steel sheet in the non-heat-affected portion is 3.0 [mu] m or less, and the C concentration at a depth of 5 [mu] m of the base material steel sheet is 0.05% or less starting from the interface between the plating layer of the plated steel sheet and the base material steel sheet in a range of 0-100 [mu] m from the bead hem portion of the welded portion in the direction opposite to the welded portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a welded joint, and more particularly to a welded joint in which LME cracking during manufacturing is suppressed. Background Art

[0002] In recent years, the strength of steel sheets used in various fields such as automobiles, home appliances, and building materials has been increasing. For example, in the automotive field, high-strength steel sheets are often arc-welded and used as welded structures in order to reduce the weight of the vehicle body in order to improve fuel efficiency.

[0003] In welding of zinc-plated steel sheets, especially high-strength steel sheets, a reduction in weldability due to liquid metal embrittlement (LME) cracking may become a problem, as described in Patent Document 1, for example. LME cracking is believed to occur because the surface layer of the steel sheet is transformed into austenite during welding, and the molten zinc that penetrates into the grain boundaries embrittles the steel sheet, and further tensile stress is applied to the steel sheet during welding.

[0004] In addition, Patent Document 2 discloses a steel plate having 3000 to 6000 pcs / mm2 of LME cracks suppressed and improved weldability. 2 The Si oxide particles having a particle size of 20 nm or more exist with a number density and an appropriate particle size distribution.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2019 / 116531

[0008] Patent Document 2: International Publication No. 2020 / 218575 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In order to prevent LME cracking during the production of welded joints, it is effective to suppress the intrusion of Zn and the like contained in the plating layer into the steel sheet after austenite transformation. In this regard, there is room for improvement.

[0011] In view of such actual conditions, an object of the present invention is to provide a lap fillet arc welded joint in which LME cracking during manufacturing is suppressed.

[0012] Means for solving problems

[0013] The inventors of the present invention have conducted intensive studies on means for solving the above-mentioned problems. As a result, they have found that by making a steel plate to be arc welded contain a large amount of Si and Al, and setting the steel plate to an appropriate surface state and performing high dew point annealing, the weld area is decarburized, and the ferrite (α) phase is stabilized, and a low C concentration in the steel plate surface layer around the weld area is maintained during the manufacture of the welded joint, thereby making it possible to suppress LME.

[0014] The present invention is based on the above-mentioned knowledge and further studies, and the gist of the present invention is as follows.

[0015] (1) A welded joint, characterized in that it is a welded joint formed by joining two plated steel plates having a tensile strength of 780 MPa or more by arc welding, the welded joint having a weld portion, a heat-affected portion, and a non-heat-affected portion, the plated steel plate having a base steel plate and a coating, the coating being formed on at least a portion of the non-heat-affected portion, the coating containing Zn, and the chemical composition of the base steel plates of the two steel plates containing, in terms of mass%, 0.05 to 0.40% C. %、Si:0.7~3.0%、Mn:0.1~5.0%、sol.Al:0.2~2.0%、P:0.0300%or less、S:0.0300%or less、N:0.0100%or less、B:0~0.010%、Ti:0~0.150%、Nb:0~0.150%、V:0~0.150%、Cr:0~2.00%、Ni:0~2.00%、Cu:0~2.00%、Mo :0~1.00%,W:0~1.00%,Ca:0~0.100%,Mg:0~0.100%,Zr:0~0.100%,Hf:0~0.100%,REM:0~0.100%,the remainder is Fe and impurities,the total content of Si and sol.Al is 1.0% or more,in the above-mentioned non-heat-affected portion,taking the interface between the coating layer of the above-mentioned plated steel sheet and the base steel sheet as the starting point,the thickness of the base steel sheet is increased along the depth direction of the above-mentioned base steel sheet. The depth at which the C concentration measured by GDS is 0.05% or less is 5 μm or more, and the roughness of the interface between the coating layer and the base steel plate in the cross section of the above-mentioned plated steel sheet is 3.0 μm or less in terms of Ra, and within the range of 0 to 100 μm from the weld bead edge of the above-mentioned welded portion in the direction opposite to the above-mentioned welded portion, with the interface between the coating layer of the above-mentioned plated steel sheet and the base steel plate as the starting point, the C concentration at a depth of 5 μm in the above-mentioned base steel plate is 0.05% or less.

[0016] (2) A weld joint according to (1) above, characterized in that, starting from the interface between the coating layer at the non-heat-affected portion of the plated steel plate and the base steel plate, the depth at which the C concentration is less than 0.05% as measured by GDS along the depth direction of the base material is 15 μm or more.

[0017] (3) The weld joint according to (1) above, wherein the roughness of the interface between the coating layer and the base steel sheet in the cross section of the plated steel sheet in the non-heat-affected portion is 2.0 μm or less in terms of Ra.

[0018] (4) A weld joint according to (1) above, characterized in that, with the interface between the coating and the base steel plate at the non-heat-affected portion of the coating steel plate as the starting point, the depth at which the C concentration is less than 0.05% as measured by GDS along the depth direction of the base steel is 15 μm or more, and the roughness of the interface between the coating and the base steel plate in the cross section of the coating steel plate at the non-heat-affected portion is less than 2.0 μm in terms of Ra.

[0019] (5) A weld joint according to any one of (1) to (4) above, characterized in that, within a range of 0 to 100 μm from the weld bead edge of the weld portion in a direction opposite to the weld portion, with the interface between the coating layer of the plated steel sheet and the base steel sheet as the starting point, the C concentration at a depth of 5 μm in the base steel sheet is not more than 0.02%.

[0020] (6) A weld joint according to any one of (1) to (4) above, characterized in that, within a range of 0 to 100 μm from the weld bead edge of the weld portion in a direction opposite to the weld portion, with the interface between the coating layer of the plated steel sheet and the base steel sheet as the starting point, the C concentration at a depth of 5 μm in the base steel sheet is not more than 0.01%.

[0021] Effects of the Invention

[0022] According to the present invention, it is possible to obtain a welded joint in which LME cracking during production is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a diagram schematically showing the periphery of a welded portion of an example of a welded joint according to the present invention.

[0024] Figure 2 This is a diagram schematically showing the periphery of a weld portion of another example of the welded joint of the present invention. DETAILED DESCRIPTION

[0025] The present invention will be described below. The present invention is not limited to the following embodiments. First, the outline of improving the LME resistance during manufacturing in the welded joint of the present invention will be described.

[0026] It is believed that LME cracking occurs due to the following factors: the surface layer of the steel plate is heated and transformed into austenite during welding, the molten zinc at the grain boundary of the plating melts and penetrates into the austenite, embrittles the steel plate, and further tensile stress is applied to the steel plate during welding. The welded joint of the present invention improves LME resistance by the structure formed in the surface layer of the steel plate constituting the welded joint. It should be noted that in this specification, the so-called surface layer of the steel plate is set to the range from the outermost surface of the steel plate to a depth of about 100 μm.

[0027] Specifically, in the welded joint of the present invention, in the non-heat-affected zone, the C concentration measured by GDS along the depth direction of the base material is less than 0.05% and the depth is 5 μm or more, with the interface between the coating layer of the plated steel plate (hereinafter sometimes referred to as "steel plate") constituting the welded joint and the base steel plate as the starting point. This means that the concentration of C, an element that easily produces LME, is low in the surface layer of the plated steel plate constituting the welded joint. Generally, when the steel plate is heated as in annealing, external oxidation that forms oxides (scale) on the surface of the steel plate occurs, decarburization becomes difficult to progress, and the C concentration in the surface layer is difficult to decrease. In the present invention, when manufacturing the steel plate constituting the welded joint, by imparting strong strain to the surface layer without increasing the surface roughness of the steel plate, the diffusion of oxygen into the material is promoted, and the C concentration in the surface layer of the steel plate can be reduced.

[0028] Furthermore, in the weld joint of the present invention, within the range of 0 to 100 μm from the weld bead edge of the weld in the direction opposite to the weld (in the direction away from the weld in the direction perpendicular to the weld boundary), the C concentration at a depth of 5 μm in the base steel plate is 0.05% or less, starting from the interface between the coating of the plated steel plate and the base steel plate. That is, even in the heat-affected zone, the C concentration becomes low. The so-called "heat-affected zone" here refers to the part of the steel plate that has not been melted and has undergone changes in the structure, metallurgical properties, mechanical properties, etc. due to welding heat. The heat-affected zone can be confirmed by observing the cross section in the plate thickness direction using SEM. It should be noted that the "non-heat-affected zone" is the part other than the heat-affected zone. The range of 0 to 100 μm from the weld bead edge of the weld in the direction opposite to the weld can be judged as the heat-affected zone.

[0029] In this case, how to form a structure in which the C concentration does not increase even under the influence of welding heat becomes a problem. The steel plate constituting the welded joint of the present invention contains a large amount of Si, which is known to reduce the LME resistance if contained in steel. This is based on the research results of the inventors of the present invention, and they have found that, contrary to the previous understanding, by containing a large amount of Si together with sol.Al, the LME resistance during the manufacture of the welded joint is improved. It is believed that this is based on the fact that by performing annealing at a high dew point during the manufacture of the steel plate, internal oxides are formed and the formation of external oxides is suppressed, thereby stabilizing ferrite by the effect of the large amount of Si contained, and ensuring a low C concentration in the surface layer of the steel plate around the weld portion during the manufacture of the welded joint.

[0030] That is, the welded joint of the present invention combines the effects of the high Si content of the steel plate constituting the welded joint, the strain imparted to the surface layer before annealing, and the control of the dew point during annealing, thereby forming a structure with a low C concentration in the surface layer of the steel plate even under the influence of heat generated by welding, thereby improving the LME resistance during the manufacture of the welded joint.

[0031] Hereinafter, the present invention will be described in detail.

[0032] The welded joint of the present invention is formed by arc welding two steel plates. The structure of the welded joint of the present invention will be described with reference to the drawings. Figure 1 The figure schematically shows the periphery of the welded portion of a welded joint formed by joining two overlapping steel plates by arc welding (lap fillet welding). Two steel plates 11 (upper plate) and 12 (lower plate) are joined by a welded portion 13 including a weld bead formed by arc welding. Figure 1 The vertical cross-sectional view shows that the steel plates 11, 12 and the weld 13 extend in the vertical direction of the paper. The weld 13 has a weld bead edge 14, which is a portion where the surface of the weld bead intersects with the surface of the steel plate. A heat-affected zone 15 is formed around the weld 13, where the structure, metallurgical properties, mechanical properties, etc. are changed by welding heat.

[0033] The welded joint of the present invention may be a welded joint formed by joining two butted steel plates by arc welding (butt welding). Figure 2 1 is a diagram schematically showing the periphery of a weld portion of a welded joint formed by butt welding. Two steel plates 21 and 22 are joined at a weld portion 23 including a weld bead formed by arc welding. Figure 2 The figure is a vertical cross-sectional view, in which the steel plates 21 and 22 and the weld 23 extend in the vertical direction of the paper. The weld 23 has a weld bead edge 24 where the surface of the weld bead intersects the surface of the steel plate. A heat-affected zone 25 is formed around the weld 23.

[0034] exist Figure 1The weld joint with lap fillet weld shown in Figure 2 In the case of the butt-welded welded joint shown in , the fact that the steel plates are joined by arc welding can be confirmed by the fact that the welded portion extends in the direction perpendicular to the paper surface.

[0035] <Chemical composition of steel sheet>

[0036] First, the chemical composition of the base steel plate of the plated steel plate constituting the welded joint is described. Hereinafter, "%" of the chemical composition is set as "mass %". In addition, in the numerical range of the chemical composition, the numerical range expressed by "to" means a range including the numerical values ​​recorded before and after "to" as the lower limit and upper limit.

[0037] (C: 0.05~0.40%)

[0038] C (carbon) is an element that ensures the strength of steel. In order to obtain a tensile strength of 780 MPa or more, which is the object of the present invention, the C content is set to 0.05-0.40% in consideration of the balance with weldability, and in order to prevent the C concentration in the surface layer of the steel plate from becoming too high. If the C content is too high, the C concentration in the surface layer of the steel plate will not decrease even through the high dew point annealing described later. The C content limit can be 0.07% or more, 0.10% or more, or 0.12% or more. The C content can be less than 0.35%, less than 0.30%, or less than 0.25%.

[0039] (Si: 0.7~3.0%, sol.Al: 0.2~2.0%, Si+sol.Al≥1.0%)

[0040] Si (silicon) is an element that promotes ferrite stabilization and decarburization by being added in combination with Al (aluminum). In order to obtain the effect of improving LME resistance, Si: 0.7-3.0%, sol.Al: 0.2-2.0%, and the total content of Si and sol.Al is set to 1.0% or more. The so-called sol.Al refers to acid-soluble Al that is not converted into oxides such as Al2O3 and is soluble in acid. It is obtained as Al measured by deducting the insoluble residue on the filter paper produced during the analysis of Al. The content of Si can be 0.8% or more, 0.9% or more, or 1.0% or more. The content of Si can be 2.8% or less, 2.5% or less, or 2.0% or less. The content of sol.Al can be 0.3% or more, 0.4% or more, or 0.5% or more. The content of sol.Al can be 1.8% or less, 1.6% or less, or 1.5% or less. The total value of the contents of Si and sol.Al may be 1.2% or more, 1.4% or more, 1.6% or more, or 1.8% or more.

[0041] (Mn: 0.1~5.0%)

[0042] Mn (manganese) is an element effective in improving the strength of steel by obtaining a hard structure. Considering the balance between the strength of steel and the reduction in workability caused by Mn segregation, the Mn content is set to 0.1-5.0%. The Mn content may be 0.5% or more, 1.0% or more, or 1.5% or more. The Mn content may be 4.5% or less, 4.0% or less, or 3.5% or less.

[0043] (P: 0.0300% or less)

[0044] P (phosphorus) is an impurity generally contained in steel. When the content of P exceeds 0.0300%, weldability may be reduced. Therefore, the content of P is set to 0.0300% or less. The content of P may be 0.0200% or less, 0.0100% or less, or 0.0050% or less. P is preferably not contained, and the lower limit of the content of P is 0%. From the viewpoint of dephosphorization cost, the content of P may be more than 0%, 0.0001% or more, or 0.0005% or more.

[0045] (S: 0.0300% or less)

[0046] S (sulfur) is an impurity generally contained in steel. When the S content exceeds 0.0300%, weldability may be reduced, and the amount of MnS precipitation increases, thereby reducing workability such as bendability. Therefore, the S content is set to 0.0300% or less. The S content can be less than 0.0100%, less than 0.0050%, less than 0.0030%, less than 0.0020% or less than 0.0010%. S is preferably not contained, and the lower limit of the S content is 0%. From the perspective of desulfurization cost, the S content can be more than 0%, more than 0.0001% or more than 0.0005%.

[0047] (N: 0.0100% or less)

[0048] N (nitrogen) is an impurity generally contained in steel. When the N content exceeds 0.0100%, weldability may be reduced. Therefore, the N content is set to 0.0100% or less. The N content may be 0.0080% or less, 0.0050% or less, 0.0030% or less, 0.0020% or less, or 0.0010% or less. N is preferably not contained, and the lower limit of the N content is 0%. From the viewpoint of manufacturing cost, the N content may be more than 0%, 0.0001% or more, 0.0002% or more, 0.0003% or more, or 0.0005% or more.

[0049] (B: 0~0.010%)

[0050] B (boron) is an element that improves hardenability and contributes to the improvement of strength, and segregates at grain boundaries to strengthen grain boundaries and improve toughness, so it can also be contained as needed. Since it is not an essential element, the lower limit of the content of B is 0%. This effect can be obtained even if it is contained in a trace amount, but the content of B in the case of containing is preferably 0.0001% or more. The content of B can be more than 0.0002%, more than 0.0003%, more than 0.0005%, more than 0.0007% or more than 0.0010%. On the other hand, from the viewpoint of ensuring sufficient toughness, the content of B is set to less than 0.010%. The content of B can be less than 0.0080%, less than 0.0060%, less than 0.0050%, less than 0.0040% or less than 0.0030%.

[0051] (Ti: 0~0.150%)

[0052] Ti (titanium) is an element that precipitates as TiC during the cooling of steel and contributes to the improvement of strength, so it can also be contained as needed. Since it is not an essential element, the lower limit of the content of Ti is 0%. This effect can be obtained even if it is contained in a trace amount, but the content of Ti in the case of containing is preferably 0.0001% or more. The content of Ti can be more than 0.0002%, more than 0.0003%, more than 0.0005%, more than 0.0007% or more than 0.0010%. On the other hand, if it is contained excessively, it is possible to generate coarse TiN and damage toughness, so the content of Ti is set to less than 0.150%. The content of Ti can be less than 0.1000%, less than 0.0500%, less than 0.0300%, less than 0.0200%, less than 0.0100%, less than 0.0050% or less than 0.0030%.

[0053] (Nb: 0~0.150%)

[0054] Nb (niobium) is an element that contributes to strength improvement by improving hardenability, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Nb content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Nb content in the case of being contained is preferably 0.001% or more. The Nb content can be 0.002% or more, 0.003% or more, 0.005% or more, or 0.008% or more. On the other hand, from the viewpoint of ensuring sufficient toughness, the Nb content is set to 0.150% or less. The Nb content can be 0.100% or less, 0.060% or less, 0.050% or less, 0.040% or less, or 0.030% or less.

[0055] (V: 0~0.150%)

[0056] V (vanadium) is an element that contributes to strength improvement by improving hardenability, so it can also be contained as needed. Since it is not an essential element, the lower limit of the V content is 0%. This effect can be obtained even if it is contained in a trace amount, but the V content in the case of containing is preferably 0.001% or more. The V content can be more than 0.002%, more than 0.003% or more than 0.005%. On the other hand, from the viewpoint of ensuring sufficient toughness, the V content is set to less than 0.150%. The V content can be less than 0.100%, less than 0.060%, less than 0.050%, less than 0.040%, less than 0.030% or less than 0.020%.

[0057] (Cr: 0~2.00%)

[0058] Cr (chromium) is effective for improving the hardenability of steel to improve the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Cr content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Cr content in the case of containing is preferably set to more than 0.001%. The Cr content can be more than 0.01%, more than 0.02%, more than 0.03%, more than 0.05% or more than 0.08%. On the other hand, if it is contained excessively, it is possible to form a large amount of Cr carbide, which will damage the hardenability on the contrary, so the Cr content is set to less than 2.00%. The Cr content can be less than 1.80%, less than 1.50%, less than 1.20%, less than 1.00%, less than 0.70%, less than 0.50% or less than 0.30%.

[0059] (Ni: 0~2.00%)

[0060] Ni (nickel) is effective for improving the hardenability of steel to improve the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the content of Ni is 0%. This effect can be obtained even if it is contained in a trace amount, but the content of Ni in the case of containing is preferably more than 0.001%. The content of Ni can be more than 0.01% or more than 0.02%. On the other hand, the excessive addition of Ni increases the cost, so the content of Ni is set to less than 2.00%. The content of Ni can be less than 1.80%, less than 1.50%, less than 1.20%, less than 1.00%, less than 0.80%, less than 0.50%, less than 0.30%, less than 0.20%, less than 0.10% or less than 0.05%.

[0061] (Cu: 0~2.00%)

[0062] Cu (copper) is effective for improving the hardenability of steel to improve the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the content of Cu is 0%. This effect can be obtained even if it is contained in a trace amount, but the content of Cu in the case of containing is preferably more than 0.0001%. The content of Cu can be more than 0.0002%, more than 0.0003% or more than 0.0005%. On the other hand, from the viewpoint of suppressing the cracking of the slab after toughness reduction and casting, the content of Cu is set to less than 2.00%. The content of Cu can be less than 1.8000%, less than 1.5000%, less than 1.2000%, less than 1.0000%, less than 0.5000%, less than 0.1000%, less than 0.0500%, less than 0.0100%, less than 0.0050%, less than 0.0030% or less than 0.0020%.

[0063] (Mo: 0~1.00%)

[0064] Mo (molybdenum) is effective for improving the hardenability of steel to improve the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Mo content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Mo content in the case of being contained is preferably 0.001% or more. The Mo content can be more than 0.01%, more than 0.02%, more than 0.03%, more than 0.05% or more than 0.08%. On the other hand, from the viewpoint of suppressing the reduction of toughness, the Mo content is set to less than 1.00%. The Mo content can be less than 0.90%, less than 0.70%, less than 0.50% or less than 0.30%.

[0065] (W: 0~1.00%)

[0066] W (tungsten) is effective for improving the hardenability of steel to improve the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the W content is 0%. This effect can be obtained even if it is contained in a trace amount, but the W content in the case of being contained is preferably 0.001% or more. The W content can be more than 0.002%, more than 0.005% or more than 0.01%. On the other hand, from the viewpoint of suppressing the reduction of toughness, the W content is set to less than 1.00%. The W content can be less than 0.90%, less than 0.70%, less than 0.50%, less than 0.30%, less than 0.10%, less than 0.05% or less than 0.03%.

[0067] (Ca: 0~0.100%)

[0068] Ca (calcium) is an element that helps control inclusions, especially fine dispersion of inclusions and has the effect of improving toughness, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Ca content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Ca content when contained is preferably 0.0001% or more. The Ca content can be 0.0002% or more. On the other hand, if it is contained in excess, the deterioration of the surface properties may be obvious, so the Ca content is set to 0.100% or less. The Ca content can be less than 0.0800%, less than 0.0500%, less than 0.0100%, less than 0.0050%, less than 0.0030%, less than 0.0020%, less than 0.0010%, less than 0.0008% or less than 0.0005%.

[0069] (Mg: 0~0.100%)

[0070] Mg (magnesium) is an element that helps control inclusions, especially fine dispersion of inclusions and has the effect of improving toughness, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Mg content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Mg content when contained is preferably 0.0001% or more. The Mg content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, or 0.0008% or more. On the other hand, if it is contained excessively, the deterioration of the surface properties may be obvious, so the Mg content is set to 0.100% or less. The Mg content can be 0.090% or less, 0.080% or less, 0.050% or less, 0.010% or less, 0.005% or less, or 0.003% or less.

[0071] (Zr: 0~0.100%)

[0072] Zr (zirconium) is an element that helps control inclusions, especially fine dispersion of inclusions and has the effect of improving toughness, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Zr content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Zr content when contained is preferably 0.001% or more. The Zr content can be more than 0.002%, more than 0.003%, more than 0.005% or more than 0.010%. On the other hand, if it is contained in excess, the deterioration of the surface properties may be obvious, so the Zr content is set to less than 0.100%. The Zr content can be less than 0.080%, less than 0.050%, less than 0.040% or less than 0.030%.

[0073] (Hf: 0~0.100%)

[0074] Hf (Hafnium) is an element that helps control inclusions, especially fine dispersion of inclusions and has the effect of improving toughness, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Hf content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Hf content when contained is preferably 0.0001% or more. The Hf content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, or 0.0008% or more. On the other hand, if it is contained in excess, the deterioration of the surface properties may be obvious, so the Hf content is set to 0.100% or less. The Hf content can be 0.050% or less, 0.030% or less, 0.010% or less, 0.005% or less, or 0.003% or less.

[0075] (REM: 0~0.100%)

[0076] REM (rare earth elements) are elements that contribute to inclusion control, especially fine dispersion of inclusions and improve toughness, so they can also be contained as needed. Since it is not an essential element, the lower limit of the REM content is 0%. This effect can be obtained even if it is contained in a trace amount, but the content of REM when contained is preferably 0.0001% or more. The content of REM can be 0.0003% or more or 0.0005% or more. On the other hand, if it is contained in excess, the deterioration of the surface properties may become obvious, so the content of REM is set to 0.100% or less. The content of REM can be 0.0500% or less, 0.0300% or less, 0.0100% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less. It should be noted that REM is the abbreviation of rare earth metal (Rare Earth Metal), which is an element belonging to the lanthanide series. REM is usually added as a mixed rare earth alloy.

[0077] In the steel plate constituting the welded joint of the present invention, the remainder other than the above chemical components includes Fe and impurities. Here, the impurities refer to components mixed in due to various factors of the manufacturing process represented by raw materials such as ore and scrap when the steel plate is industrially manufactured, and are components that do not adversely affect the LME resistance when the welded joint of the present invention is manufactured.

[0078] The chemical composition of the steel plate can be analyzed by an elemental analysis method known to those skilled in the art, for example, by inductively coupled plasma mass spectrometry (ICP-MS). However, it is preferable to use a combustion-infrared absorption method for C and S, and to use an inert gas melting-thermal conductivity method for N. These analyses can be performed on samples collected from the steel plate by a method in accordance with JIS G0417:1999.

[0079] The plated steel plate constituting the welded joint of the present invention comprises: a base steel plate; and a Zn-containing plating layer formed on the surface of the base steel plate, at least a portion of the surface corresponding to the non-heat-affected portion during welding. The plating layer is not particularly limited as long as it contains Zn. As an example, Zn-0.2% Al, Zn-0.5% Al, Zn-1.5%-Al-1.5% Mg, Zn-20% Al-7% Mg, and Zn-30% Al-10% Mg can be listed. The plating layer can also be formed on a surface other than the surface corresponding to the non-heat-affected portion.

[0080] The chemical composition of the coating can be determined by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the steel sheet is added, and measuring the obtained solution by ICP (high frequency inductively coupled plasma) emission spectrometry. The acid solution to which the inhibitor is added can be, for example, a 10 mass % hydrochloric acid solution to which 0.06 mass % inhibitor (manufactured by Asahi Chemical Industry Co., Ltd., IBIT) is added.

[0081] The thickness of the plating layer may be, for example, 3 to 50 μm. The amount of the plating layer applied is not particularly limited, but may be, for example, 10 to 170 g / m per side. 2 In the present invention, the coating adhesion amount is determined by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the base steel plate is added, and the weight change of the coating before and after pickling and stripping is determined. The coating thickness may be greater than 5 μm, greater than 10 μm, greater than 15 μm, or greater than 20 μm. The coating thickness may be less than 40 μm or less than 30 μm. The coating adhesion amount may be 20 g / m per single side. 2 Above, 30g / m 2 Above, 40g / m 2 Above or 50g / m 2 The coating weight can be 150g / m per side. 2 Below, 130g / m 2 Below, 120g / m 2 Below or 100g / m 2 the following.

[0082] The thickness of the steel plate constituting the welded joint of the present invention is not particularly limited. For example, it can be set to 0.6 to 3.2 mm. The thickness can be 0.8 mm or more or 1.0 mm or more. The thickness can be 3.0 mm or less, 2.6 mm or less, 2.4 mm or less, 2.2 mm or less, 2.0 mm or less, or 1.8 mm or less.

[0083] <Structure of Steel Plates Constituting Welded Joints>

[0084] Next, the structure of the steel plate constituting the welded joint will be described.

[0085] [C concentration in non-heat-affected zone]

[0086] In the welded joint of the present invention, the interface between the coating layer and the base steel plate at the non-heat-affected portion of the steel plate is taken as the starting point, and the depth at which the C concentration is 0.05% or less as measured by GDS along the depth direction of the base steel is 5 μm or more. The heat-affected portion can be confirmed by SEM observation of the portion where the material properties change due to heat during arc welding. The non-heat-affected portion is the portion other than the heat-affected portion.

[0087] Since the sensitivity to LME decreases as the C concentration decreases, the LME resistance during the production of the welded joint is improved by reducing the C concentration in the non-heat-affected zone.

[0088] Such a structure can be obtained by setting the chemical composition of the steel plate to a composition containing a large amount of Si and Al as described above, performing a heat treatment described later, and performing arc welding.

[0089] If the depth at which the C concentration is 0.05% or less is 5 μm or more, the effect of improving the LME resistance during manufacturing can be obtained, so the upper limit of the depth is not particularly limited, and the depth may be, for example, 50 μm or less, 40 μm or less, or 30 μm or less. The depth at which the C concentration is 0.05% or less may be 7 μm or more, 8 μm or more, 10 μm or more, or 12 μm or more, and preferably 15 μm or more.

[0090] GDS measurement was performed 5 times along the plate thickness direction, and the average value was taken as the C concentration. The measurement conditions were set as follows. The starting point of the "depth" was the interface between the base steel plate and the coating. The interface between the base steel plate and the coating was set to the position where the Fe concentration measured by GDS measurement became 93% of the Fe concentration at a depth of 150 μm.

[0091] Equipment: High-frequency glow discharge luminescence analyzer (manufactured by LECO JAPAN Co., Ltd., model "GDS850A"

[0092] Ar gas pressure: 0.3MPa

[0093] Anode diameter: 4mmφ

[0094] RF output power: 30W

[0095] Measuring time: 200 to 1500 seconds

[0096] [Interface roughness at non-heat-affected zone]

[0097] In the welded joint of the present invention, the roughness of the interface between the coating and the base steel plate in the cross section of the steel plate in the non-heat-affected portion is 3.0 μm or less in terms of the arithmetic mean height Ra defined in JIS B0601:2013. If the roughness increases, cracking becomes more likely to occur due to stress concentration. The roughness of the interface can be 2.5 μm or less or 2.0 μm or less in terms of Ra. The roughness of the interface can be set to the surface roughness of the steel plate measured after the coating is removed. The coating is removed by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the steel plate is added.

[0098] [C concentration outside the weld bead edge]

[0099] In the weld joint of the present invention, within the range of 0 to 100 μm from the weld bead edge of the weld in the direction opposite to the weld (the direction away from the weld in the direction perpendicular to the weld boundary), with the interface between the coating of the steel plate and the base steel plate as the starting point, the C concentration at a depth of 5 μm in the base steel plate is less than 0.05%.

[0100] Since the sensitivity to LME decreases as the C concentration decreases, the LME resistance during the production of the welded joint is improved by reducing the C concentration outside the bead edge portion of the weld.

[0101] Furthermore, if the C concentration at a depth of 5 μm in the base steel plate is 0.02% or less, starting from the interface between the plated layer of the steel plate and the base steel plate in the range of 0 to 100 μm from the bead edge of the weld in the direction opposite to the weld, it is preferred from the viewpoint of improving LME resistance. The C concentration at a depth of 5 μm in the base steel plate starting from the interface between the plated layer of the steel plate and the base steel plate in the range of 0 to 100 μm in the direction opposite to the weld is more preferably 0.01% or less.

[0102] The C concentration is measured by SEM-EPMA. The measurement method is as follows. An observation sample is cut out from the weld joint in a range of 0 to 100 μm outside the weld bead edge, and the cross section in the thickness direction of the steel plate is mirror-polished. Next, using EPMA, the polished observation sample is point analyzed by the standard line method. The so-called point analysis refers to a quantitative analysis in which the measurement range is set to a diameter of 0 μm. As an EPMA apparatus, for example, JXA-8500 manufactured by JEOL Ltd. can be used. The analysis conditions of EPMA are set as follows: an acceleration voltage of 15 kV and an irradiation current of 5×10 -7 A. The observation magnification was set to 5000 times. As for the standard line, Fe-0.01%C, Fe-0.05%C, and Fe-0.10%C alloys were prepared, and the average C concentration of the alloys was measured under the above-mentioned conditions.

[0103] The measurement using point analysis was performed at a depth of 5 μm starting from the interface between the coating layer of the steel plate and the base steel plate, and the range of 0 to 100 μm outside the weld edge was measured at 5 μm scale, and the average value of the measured values ​​at each position was taken as the C concentration at a depth of 5 μm in the range of 0 to 100 μm in the opposite direction of the weld.

[0104] [Tensile strength of steel plate]

[0105] Since the present invention suppresses the generation of LME in the high-strength steel plate, the steel plate constituting the welded joint is high-strength. Specifically, it has a tensile strength of 780 MPa or more. The upper limit of the tensile strength is not particularly limited, but from the viewpoint of ensuring toughness, for example, it can be 2000 MPa or less. Regarding the measurement of tensile strength, a JIS No. 5 tensile test piece with a direction perpendicular to the rolling direction as the length direction is collected and carried out in accordance with JIS Z 2241:2011. The tensile strength can be 880 MPa or more, 980 MPa or more, 1080 MPa or more, or 1180 MPa or more. The tensile strength can be 1900 MPa or less, or 1800 MPa or less.

[0106] It should be noted that when it is impossible to collect a test piece for measuring the tensile strength from the steel plate constituting the welded joint, the hardness (Vickers hardness) of the steel plate at the non-heat-affected portion at a distance of more than 5 mm from the outer end of the spot weld can be measured as an alternative, and the value of the tensile strength can be estimated by the following correlation formula (Correlation between static strength parameters, Norihiko Hasegawa, Junichi Arai, Michishichi Tanaka, "Materials" Vol. 39, No. 442, P859-863).

[0107] Hv=0.301×TS+5.701

[0108] (Wherein, Hv is Vickers hardness, TS is tensile strength (unit: MPa))

[0109] That is, if the hardness is about 240 Hv or more, it can be considered that the tensile strength is 780 MPa or more.

[0110] The hardness of the steel plate is measured at the position of the non-heat-affected portion of the steel plate constituting the welded joint and at a position of 1 / 2 depth. The hardness measurement is performed in accordance with JIS Z 2244:2009. The measurement load is set to 200 gf. The hardness of the steel plate at the non-heat-affected portion at a distance of 5 mm or more from the outer end of the spot weld can be 245 Hv or more, 250 Hv or more, 260 Hv or more, 270 Hv or more, 300 Hv or more, or 340 Hv or more.

[0111] Next, a method for manufacturing a welded joint according to the present invention will be described. First, a method for manufacturing a steel plate constituting a welded joint will be described.

[0112] The steel plate constituting the welded joint of the present invention can be obtained, for example, by a manufacturing method having the following steps: a casting step of casting a steel molten steel having an adjusted chemical composition to form a steel billet; a hot rolling step of hot rolling the steel billet to obtain a hot-rolled steel plate; a coiling step of coiling the hot-rolled steel plate; a cold rolling step of cold rolling the coiled hot-rolled steel plate to obtain a cold-rolled steel plate; a pre-treatment step of brushing and grinding the cold-rolled steel plate; and an annealing step of annealing the pre-treated cold-rolled steel plate. Alternatively, the hot rolling step may be replaced by a step of directly cold rolling after pickling without coiling.

[0113] [Casting process]

[0114] The conditions of the casting process are not particularly limited. For example, after melting in a blast furnace, electric furnace, etc., various secondary refinings are performed, and then casting is performed by a method such as ordinary continuous casting or casting by an ingot casting method.

[0115] [Hot rolling process]

[0116] The steel billet obtained by casting can be hot-rolled to obtain a hot-rolled steel plate. The hot rolling process is carried out by directly hot-rolling the cast steel billet or by temporarily cooling it and then reheating it. In the case of reheating, the heating temperature of the steel billet can be, for example, 1100 to 1250°C. In the hot rolling process, rough rolling and finish rolling are usually carried out. The temperature and reduction rate of each rolling can be appropriately changed according to the desired metal structure and plate thickness. For example, the end temperature of the finish rolling can be 900 to 1050°C, and the reduction rate of the finish rolling can be 10 to 50%.

[0117] [Coiling process]

[0118] The hot rolled steel sheet can be coiled at a predetermined temperature. The coiling temperature can be appropriately changed according to the desired metal structure, for example, 500 to 800°C. The hot rolled steel sheet can also be uncoiled before or after coiling and subjected to a predetermined heat treatment. Alternatively, the hot rolled steel sheet can be pickled after the hot rolling process without coiling and then cold rolled as described below.

[0119] [Cold rolling process]

[0120] After pickling the hot-rolled steel sheet, the hot-rolled steel sheet can be cold-rolled to obtain a cold-rolled steel sheet. The cold-rolling reduction ratio can be appropriately changed according to the desired metal structure and plate thickness, for example, 20 to 80%. After the cold-rolling process, for example, air cooling can be performed to cool to room temperature.

[0121] [Pre-treatment process]

[0122] In order to set the depth at which the C concentration is 0.05% or less measured by GDS in the depth direction of the base material to 5 μm or more in the welded joint with the interface between the coating layer and the base material steel plate at the non-heat-affected portion of the steel plate as the starting point as described above, and to set the C concentration at a depth of 5 μm in the base material steel plate to 0.05% or less in the range of 0 to 100 μm from the weld bead edge of the weld portion in the direction opposite to the weld portion, it is necessary to perform a prescribed pretreatment before annealing of the steel plate and then perform annealing.

[0123] The pretreatment includes grinding the surface of the cold-rolled steel sheet with a grinding brush (brush grinding treatment). As an example of a grinding brush that can be used, M-33 manufactured by HOTANI Corporation can be cited. In this way, strain can be introduced without increasing the roughness of the surface. It is appropriate to apply a 1.0-5.0% aqueous solution of NaOH on the surface of the steel sheet during grinding. It is appropriate that the brush pressure reduction is 0.5-10.0 mm and the rotation speed is 100-1000 rpm. By controlling the coating liquid conditions, brush pressure reduction, and rotation speed to perform the brush grinding treatment, decarburization is promoted in the annealing process described later, and a ferrite-stable structure is effectively formed in the surface layer of the steel sheet, so that a low C concentration around the weld can be ensured during the manufacture of the welded joint.

[0124] [Annealing process]

[0125] After the pretreatment step, the cold-rolled steel sheet is annealed. Annealing is performed under a tension of 1 to 20 MPa. If tension is applied during annealing, strain can be more effectively introduced into the steel sheet, promoting decarburization of the surface layer.

[0126] The holding temperature of the annealing process is set to 750-900°C. The holding temperature may be 770-870°C. By setting it in such a range, decarburization can be promoted, the C concentration of the surface layer can be reduced, and the ferrite phase can be stabilized. The heating rate until the holding temperature is not particularly limited, but it can be carried out at 1-10°C / second.

[0127] The holding time at the holding temperature in the annealing process is set to 20 to 300 seconds. The holding time may be 30 to 250 seconds. By setting it within such a range, decarburization can be promoted, the C concentration in the surface layer can be reduced, and the ferrite phase can be stabilized.

[0128] The dew point of the atmosphere in the annealing process is set to -30 to 20°C. The dew point can be -10 to 5°C. The atmosphere can be, for example, N2-1 to 10 vol% H2, or N2-2 to 4 vol% H2. If the dew point is too high or too low, a phase containing oxides such as Si, Mn, and Al may be formed outside the steel sheet, which may hinder the mutual diffusion of the plating components and the steel components, and the plating property may become insufficient.

[0129] The production method including the above steps can provide a steel plate in which decarburization is promoted in the surface layer of the steel plate, the ferrite phase is stabilized, and a low C concentration around the weld can be maintained during weld joint production.

[0130] <Method for producing plated steel sheet>

[0131] The plated steel sheet constituting the weld joint of the present invention can be obtained by performing a plating treatment to form a plated layer containing Zn on the steel sheet manufactured as described above.

[0132] The plating treatment can be carried out according to methods known to those skilled in the art. The plating treatment can be carried out, for example, by hot-dip plating or by electroplating. Preferably, the plating treatment is carried out by hot-dip plating. The conditions of the plating treatment can be appropriately set by considering the chemical composition, thickness and adhesion amount of the desired coating. For example, it can be immersed in a hot-dip galvanizing bath of 420 to 480°C with adjusted chemical composition for 1 to 10 seconds, and then removed at 20 to 200 mm / second after immersion, and the coating adhesion amount can be controlled by N2 wiping gas, or alloying treatment can be carried out after the plating treatment. The alloying treatment can be carried out, for example, at 500 to 550°C for 10 to 60 seconds.

[0133] <Arc welding process>

[0134] The two steel plates are overlapped or butted and arc welded to obtain a welded joint. The welding conditions and the welding wire used for arc welding are not particularly limited, and for example, arc welding can be performed at a welding current of 80 to 300 A, a welding voltage of 15 to 35 V, a welding speed of 50 to 200 cm / min, and a welding gas of 10 to 30% CO2+Ar and a flow rate of 10 to 30 L / min.

[0135] Since the welded joint of the present invention can suppress LME cracking during production, it can be suitably used in a wide range of fields such as automobiles, home electrical appliances, and building materials, and is particularly preferably used in the automobile field.

[0136] Example

[0137] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.

[0138] <Example 1>

[0139] (Preparation of Steel Plate Samples)

[0140] The molten steel adjusted to the chemical composition described in No. 1 of Table 1 was melted in a blast furnace and cast by continuous casting to obtain a steel billet. The obtained steel billet was heated to 1200°C, and the finishing temperature of the finish rolling was set to 950°C and the reduction rate of the finish rolling was set to 30% to perform hot rolling to obtain a hot-rolled steel plate. The obtained hot-rolled steel plate was coiled at a coiling temperature of 650°C, pickled, and then cold rolled at a reduction rate of 50% to obtain a cold-rolled steel plate. The plate thickness of the cold-rolled steel plate was set to 1.6 mm.

[0141] Next, a 2.0% aqueous solution of NaOH was applied to the cold-rolled steel sheet for brush polishing. The brush polishing was performed using a polishing brush M-33 manufactured by Hotani Co., Ltd. at a brush pressure of 2.0 mm and a rotation speed of 600 rpm (Condition A in Table 2).

[0142] Before the annealing process, the surface roughness of the steel sheet was measured in accordance with JIS B 0601: 2013. That is, 10 locations were randomly selected on the surface of the surface layer side, the surface profile was measured at each location using a contact type surface roughness meter, and the arithmetic average roughness Ra obtained by arithmetically averaging the surface roughness at these locations was evaluated as follows.

[0143] Evaluation AA: 2.0μm or less

[0144] Evaluation A: more than 2.0 μm and 3.0 μm or less

[0145] Evaluation B: more than 3.0 μm

[0146] After that, the steel plate samples were prepared by annealing in a furnace with an oxygen concentration of 20 ppm or less in a N2-4% H2 gas atmosphere with a dew point of 0°C, a holding temperature of 800°C, and a holding time of 20 seconds. The heating rate during annealing was set to 6.0°C / second until 500°C, and 2.0°C / second from 500°C to the holding temperature. The annealing was performed under a tension of 15 MPa.

[0147] After annealing, the steel sheet is plated to obtain a hot-dip galvanized steel sheet. The plated steel sheet is immersed in a hot-dip galvanizing bath (Zn-0.2% Al) at 460°C for 3 seconds. After immersion, the steel sheet is removed at a speed of 100 mm / sec and the coating weight is controlled to 50 g / m by N2 wiping gas. 2 .

[0148] <Examples 2 to 28, Comparative Examples 29 to 41>

[0149] The steel sheet was manufactured in the same manner as in Example 1 except that the chemical composition was set to the composition described in Table 1, the conditions of the pretreatment process and the annealing process were set to the conditions described in Table 2, and the plating type was set to the plating type described in Table 3. It should be noted that the pretreatment of brush grinding was omitted in No. 40. In addition, in No. 41, a grinding brush D-100 manufactured by HOTANI Co., Ltd. was used (Condition B in Table 2). D-100 is a brush with a grinding amount about twice that of M-33.

[0150] The composition and bath temperature of the plating species shown in Table 3 are as follows: F After the plating treatment, alloying treatment was performed at 530° C. for 20 seconds to obtain alloyed hot-dip galvannealing.

[0151] A: Zn-0.2%Al (460℃)

[0152] B: Zn-0.5%Al (440℃)

[0153] C: Zn-1.5%Al-1.5%Mg (500℃)

[0154] D: Zn-20%Al-7%Mg (530℃)

[0155] E: Zn-30%Al-10%Mg (530℃)

[0156] F: Zn-0.14%Al (450℃) alloyed hot-dip galvanized

[0157] Table 1

[0158]

[0159] ※ The underlined elements are outside the scope of the present invention.

[0160] Table 2

[0161]

[0162] ※ The underlined elements are outside the range of the preferred production method.

[0163] (Tensile Strength Evaluation)

[0164] For each steel plate, a JIS No. 5 tensile test piece having a longitudinal direction perpendicular to the rolling direction was collected and subjected to a tensile test in accordance with JIS Z 2241:2011 to obtain the tensile strength, which was evaluated as follows.

[0165] Rating AAA: 1180MPa or above

[0166] Evaluation AA: 980MPa or more and less than 1180MPa

[0167] Evaluation A: 780MPa or more and less than 980MPa

[0168] (Evaluation of LME resistance)

[0169] For each steel plate, two identical steel plates were subjected to gas shielded arc welding to form a weld bead, thereby producing a lap fillet weld joint, and the LME suppression effect (LME resistance) during production was evaluated. The welding conditions were set as follows.

[0170] Welding current: 250A

[0171] Welding voltage: 26.2V

[0172] Welding speed: 80cm / min

[0173] Welding gas: 20% CO2+Ar, flow rate: 20L / min

[0174] Welding wire: YM-24T (φ1.2mm) manufactured by Nippon Steel Welding Industry Co., Ltd.

[0175] Inclination angle of welding torch: 60°

[0176] Overlap: 10mm

[0177] Steel plate size: upper plate side 150×50mm, lower plate side 150×30mm

[0178] Plate gap: 0mm

[0179] Wire extension length: 15mm

[0180] The LME resistance was evaluated as follows based on the length of the generated LME cracks. If the evaluation was "A" or higher, it was determined that the LME resistance was excellent and the problem to be solved by the present invention was solved.

[0181] Rating AAA: 0μm

[0182] Evaluation AA: more than 0μm and less than 60μm

[0183] Evaluation A: 60 μm or more and less than 120 μm

[0184] Evaluation B: 120μm or more

[0185] (Evaluation of the structure around the weld)

[0186] The welded joint was cut to collect a sample, and GDS measurements were performed five times along the thickness direction at the position of the non-heat-affected zone, with the interface between the coating and the base steel plate as the starting point, to determine the depth at which the C concentration was less than 0.05%, which is shown in "C ≤ 0.05% depth" in Table 3.

[0187] In addition, at the position that becomes the non-heat-affected zone, the plating layer is removed using a 10 mass % hydrochloric acid solution to which 0.06 mass % inhibitor (manufactured by Asahi Chemical Industries, Ltd., IBIT) is added, and the roughness of the surface of the exposed steel plate is measured by the same method as before annealing, and is shown in the "base steel plate / plating interface roughness" of Table 3.

[0188] In addition, at a position of 0 to 100 μm from the weld bead side of the lower plate side of the welded portion in the direction opposite to the welded portion, the C concentration at a depth of 5 μm in the base steel plate was measured by SEM-EPMA, starting from the interface between the plated layer of the steel plate and the base steel plate, and is shown in "C concentration" in Table 3. The measurement method was set as follows.

[0189] From the welded joint, the observation sample was cut out in a manner including a range of 0 to 100 μm from the weld bead edge to the direction opposite to the weld, and the cross section in the thickness direction of the steel plate was mirror polished. Next, the polished observation sample was point analyzed by the standard line method using EPMA. As an EPMA apparatus, JXA-8500 manufactured by JEOL Ltd. was used. The analysis conditions of EPMA were set as follows: acceleration voltage of 15 kV, irradiation current of 5 × 10 -7 A, the observation magnification was set to 5000. As the standard line, a standard line prepared by measuring the average C concentration of Fe-0.01%C, Fe-0.05%C, and Fe-0.10%C alloys was used.

[0190] The measurement using point analysis was performed at a depth of 5 μm starting from the interface between the coating layer of the steel plate and the base steel plate, and in a range of 0 to 100 μm from the weld edge in the direction opposite to the weld portion, with the average value of the measured values ​​at each position being taken as the C concentration at a depth of 5 μm in the range of 0 to 100 μm.

[0191] Table 3 shows the results of each evaluation.

[0192] Table 3

[0193]

[0194] ※ The underlined elements are outside the scope of the present invention or do not provide the expected properties.

[0195] No. 29 is a comparative example in which the C content of the steel plate is high. It is believed that since the C content of the steel plate is high, decarburization in the surface layer does not progress even through high dew point annealing. Therefore, the depth at which the C concentration measured by GDS is 0.05% or less in the non-heat-affected zone becomes smaller, and the C concentration at a position of 0 to 100 μm in the opposite direction from the weld bead edge becomes higher. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0196] No. 30 is a comparative example in which the Si content of the steel plate is small and the sum of the Si and sol. Al contents is small. It is believed that since the Si content of the steel plate is small and the sum of the Si and sol. Al contents is small, even if high dew point annealing is performed, decarburization in the surface layer does not progress and ferrite is not stabilized. Therefore, the depth at which the C concentration measured by GDS in the non-heat-affected zone is 0.05% or less becomes smaller, and the C concentration at a position of 0 to 100 μm in the opposite direction from the weld bead edge becomes higher. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0197] No. 31 is a comparative example in which the Si content of the steel plate is low. It is believed that since the Si content of the steel plate is low, even if high dew point annealing is performed, decarburization in the surface layer does not progress, and ferrite is not stabilized. Therefore, the depth at which the C concentration measured by GDS is 0.05% or less in the non-heat-affected zone becomes smaller, and the C concentration at a position of 0 to 100 μm in the opposite direction from the weld bead edge becomes higher. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0198] No. 32 is a comparative example in which the Si content of the steel plate is high. It is believed that since the Si content of the steel plate is high, even if high dew point annealing is performed, external oxidation progresses and oxides (scale) are formed in the surface layer of the steel plate, suppressing decarburization at the outermost surface. Therefore, the depth at which the C concentration measured by GDS in the non-heat-affected zone is 0.05% or less becomes smaller, and the C concentration at a position of 0 to 100 μm from the weld edge to the opposite direction of the weld becomes higher. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0199] No. 33 is a comparative example in which the sol. Al content of the steel plate is small. It is believed that since the sol. Al content of the steel plate is small, even if high dew point annealing is performed, decarburization in the surface layer does not progress, and ferrite is not stabilized. Therefore, the depth at which the C concentration measured by GDS is 0.05% or less in the non-heat-affected zone becomes smaller, and the C concentration at a position of 0 to 100 μm in the opposite direction from the weld bead edge becomes higher. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0200] No. 34 is a comparative example in which the sol. Al content of the steel plate is high. It is believed that since the sol. Al content of the steel plate is high, even if high dew point annealing is performed, external oxidation progresses and oxides (scale) are formed in the surface layer of the steel plate, which inhibits decarburization at the outermost surface. Therefore, the C concentration at the position of 0 to 100 μm in the direction opposite to the weld part from the weld bead edge becomes high. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0201] No. 35 is a comparative example in which the sum of the Si and sol. Al contents of the steel plate is small. It is believed that since the sum of the Si and sol. Al contents of the steel plate is small, even if high dew point annealing is performed, decarburization in the surface layer does not progress, and ferrite is not stabilized. Therefore, the depth at which the C concentration measured by GDS in the non-heat-affected zone is 0.05% or less becomes smaller, and the C concentration at a position of 0 to 100 μm from the weld edge to the opposite direction of the weld becomes higher. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0202] It is believed that since the dew point of No. 36 was low during annealing, a phase containing oxides such as Si, Mn, and Al was formed on the outside of the steel sheet during annealing, which hindered the mutual diffusion of the plating components and the steel components during the plating treatment. As a result, since appropriate plating was not obtained, the weld joint was not evaluated.

[0203] It is believed that since the dew point of No. 37 was high during annealing, a phase containing oxides such as Si, Mn, and Al was formed on the outside of the steel sheet during annealing, which hindered the mutual diffusion of the plating components and the steel components during the plating treatment. As a result, since appropriate plating was not obtained, the weld joint was not evaluated.

[0204] It is believed that since the holding temperature during annealing of No. 38 was low, decarburization was not sufficiently promoted during annealing. Therefore, the depth at which the C concentration was 0.05% or less measured by GDS in the non-heat-affected zone became smaller, and the C concentration at the position of 0 to 100 μm in the direction opposite to the welded portion from the weld bead edge became higher. As a result, the LME resistance during the manufacture of the welded joint was inferior.

[0205] It is believed that in No. 39, the holding temperature during annealing was high, so decarburization was not sufficiently promoted during annealing. Therefore, the depth at which the C concentration in the non-heat-affected zone measured by GDS was 0.05% or less became smaller, and the C concentration at the position of 0 to 100 μm from the bead edge to the opposite direction of the weld became higher. As a result, the LME resistance during the manufacture of the welded joint was inferior.

[0206] It is believed that since the holding time during annealing of No. 40 was short, decarburization was not sufficiently promoted during annealing. Therefore, the depth at which the C concentration was 0.05% or less measured by GDS in the non-heat-affected zone became smaller, and the C concentration at the position of 0 to 100 μm in the direction opposite to the welded portion from the weld bead edge became higher. As a result, the LME resistance during the manufacture of the welded joint was inferior.

[0207] It is believed that since brush polishing was not performed in the pre-treatment process, no strain was introduced on the surface of the steel plate in No. 41, and decarburization did not progress during annealing. Therefore, the C concentration at the position of 0 to 100 μm in the opposite direction from the weld bead edge became high. As a result, the LME resistance during the manufacture of the welded joint was poor.

[0208] It is believed that since a brush with a large grinding amount was used in the brush grinding of the pre-treatment process in No. 42, the roughness of the steel plate surface became large and the ferrite phase was not stable. Therefore, the C concentration at the position of 0 to 100 μm from the weld edge to the opposite direction of the weld portion became high. As a result, the LME resistance during the manufacture of the welded joint was poor.

[0209] No. 1 to 28 are examples of the present invention, which suppress LME during the manufacture of welded joints. The examples in which the depth of the C concentration in the non-heat-affected zone is large and the C concentration in the position of 0 to 100 μm from the bead edge to the opposite direction of the weld zone is small confirmed to have particularly excellent LME resistance.

[0210] Industrial Applicability

[0211] According to the present invention, a weld joint in which LME cracking during production is suppressed can be provided, and the weld joint can be suitably used for applications such as automobiles, home appliances, and building materials, especially for automobiles. Therefore, the present invention has extremely high industrial applicability.

[0212] Explanation of symbols

[0213] 11 steel plate (upper plate)

[0214] 12 Steel plate (lower plate)

[0215] 13 Welding Department

[0216] 14 Weld bead edge

[0217] 15 Heat affected area

[0218] 21 Steel Plate

[0219] 22 Steel Plate

[0220] 23 Welding Department

[0221] 24 Weld bead edge

[0222] 25 Heat affected area

Claims

1. A welding joint, characterized in that: It is a welded joint formed by joining two plated steel plates with a tensile strength of 780 MPa or more by arc welding. The weld joint comprises a weld portion, a heat-affected portion and a non-heat-affected portion. The plated steel sheet comprises a base steel sheet and a plated layer, wherein the plated layer is formed on at least a portion of the non-heat-affected portion, and the plated layer contains Zn. The chemical composition of the parent steel plates of the two steel plates is expressed in mass % as follows: C:0.05~0.40%、 Si: 0.7-3.0%, Mn: 0.1-5.0%, Sol.Al: 0.2~2.0%, P: 0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B:0~0.010%、 Ti: 0~0.150%, Nb: 0~0.150%, V:0~0.150%、 Cr:0~2.00%、 Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W:0~1.00%、 Ca: 0~0.100%, Mg: 0~0.100%, Zr:0~0.100%、 Hf: 0~0.100%、 REM: 0~0.100%, the rest is Fe and impurities, The total content of Si and sol.Al is 1.0% or more. In the non-heat-affected zone, with the interface between the coating layer of the plated steel sheet and the base steel sheet as the starting point, the depth at which the C concentration is 0.05% or less as measured by GDS in the depth direction of the base steel sheet is 5 μm or more, and the roughness of the interface between the coating layer and the base steel sheet in the cross section of the plated steel sheet is 3.0 μm or less in terms of Ra, and within the range of 0 to 100 μm from the weld bead edge of the weld portion in the direction opposite to the weld portion, with the interface between the coating layer of the plated steel sheet and the base steel sheet as the starting point, the C concentration of the base steel sheet at a depth of 5 μm is 0.05% or less.

2. The welded joint according to claim 1, characterized in that: The depth at which the C concentration is 0.05% or less as measured by GDS in the depth direction of the base material is 15 μm or more, starting from the interface between the plating layer and the base material steel sheet in the non-heat-affected portion of the plated steel sheet.

3. The welded joint according to claim 1, characterized in that: The roughness of the interface between the plating layer and the base steel sheet in the cross section of the plated steel sheet in the non-heat-affected portion is 2.0 μm or less in terms of Ra.

4. The welded joint according to claim 1, characterized in that: The depth at which the C concentration is 0.05% or less as measured by GDS along the depth direction of the base material is 15 μm or more, starting from the interface between the coating layer and the base material steel sheet at the non-heat-affected portion of the plated steel sheet, The roughness of the interface between the plating layer and the base steel sheet in the cross section of the plated steel sheet in the non-heat-affected portion is 2.0 μm or less in terms of Ra.

5. The welded joint according to any one of claims 1 to 4, characterized in that: In the range of 0 to 100 μm from the weld bead edge of the weld portion in the direction opposite to the weld portion, with the interface between the coating layer of the plated steel sheet and the base steel sheet as the starting point, the C concentration of the base steel sheet at a depth of 5 μm measured by GDS is 0.02% or less.

6. The welded joint according to any one of claims 1 to 4, characterized in that: In the range of 0 to 100 μm from the weld bead edge of the weld portion in the direction opposite to the weld portion, with the interface between the coating layer of the plated steel sheet and the base steel sheet as the starting point, the C concentration of the base steel sheet at a depth of 5 μm measured by GDS is 0.01% or less.

Citation Information

Patent Citations

  • Steel sheet, hot-dip zinc-coated steel sheet, and alloyed hot-dip zinc-coated steel sheet

    WO2019116531A1

  • Steel sheet

    WO2020218575A1